Reinforcement learning and meta-learning perspectives frameworks for future medical imaging - Huda, Nurul; Windiarti , Ika Safitri (Association for Scientific Computing Electrical and Engineering, 2024)
In the envisioned landscape of medical imaging in 2044, this research explores the integration of advanced AI techniques, specifically reinforcement learning (RL) and meta-learning, to address persistent challenges in disease diagnosis and treatment planning. Leveraging vast amounts of imaging data, deep learning models have demonstrated significant advancements in tasks such as tumor detection and organ segmentation. However, existing approaches often face limitations in adapting to evolving patient characteristics and data scarcity. By incorporating principles from RL and meta-learning, this study aims to develop dynamic, adaptive AI systems capable of optimizing imaging protocols, enhancing diagnostic accuracy, and personalizing treatment strategies for individual patients. The research conducts a comprehensive review of existing literature on RL and meta-learning in healthcare proposes novel methodologies for integrating these techniques into medical imaging workflows, and evaluates their efficacy through empirical studies and clinical validation. The ultimate goal is to contribute to the advancement of medical imaging technologies, paving the way for more personalized and efficient healthcare solutions in the future